Studying and Analyzing the Immersion Scenario on Latakia Coast using Geographic Information Systems - ابراهيم, فينوس; علاءالدين, محمد دريد; حماد, منذر (Latakia University Journal -Engineering Sciences Series, 2025)
Studying the scenario of inundation resulting from sea level rise is one of the vital aspects in the field of environmental and engineering sciences, especially with the increasing climate change and its escalating impact on the coastal environment. This research aims to quantitatively estimate the impacts of sea level rise and the development of potential flood scenarios in the coastal region in Lattakia governorate in Syria. The research relies on the use of Geographic Information Systems (GIS) to collect and analyze relevant spatial data, which enables us to draw maps showing areas at risk based on expected sea level rise scenarios. In addition to using analytical models to estimate the potential impacts of floods and specifically on water resources, which helps in developing planning policies and adaptation measures that enhance resilience and sustainability in the face of climate change challenges on the coasts. In addition to taking appropriate preventive measures to reduce potential negative effects, which may reach the point of affecting the lives of humans and living organisms in the affected areas. Analysis of the inundation scenarios (1.00 m, 1.50 m, 8.82 m) revealed the presence of dangerous indicators of damage to water resources adjacent to the coast of Lattakia governorate, especially rivers, irrigation canals, barmaids and waterways, as well as wells, water tanks, springs. According to the simulation, flooded areas reached (10.29 km2, 13.12 km2, 55.59 km2) respectively for scenarios (1.00 m, 1.50 m, 8.82 m), and the estimated damage were (16,674 km) of rivers, (24,405 km) of irrigation canals, (14,171 km) of barmaids, and (17,972 km) of waterways within the most dangerous inundation scenario (8.82 m).